Guidelines for Increasing the Effectiveness of Thailand’s Sustainable Development Policy based on Energy Consumption: Enriching the Path-GARCH Model - Sutthichaimethee, Pruethsan; Sutthichaimethee, Jindamas; Vutikorn, Chittinan; Ariyasajjakorn, Danupon; Wongthongdee, Sirapatsorn; Siriwattana, Srochinee; Chatchorfa, Apinyar; Khomchunsri, Borworn (International Journal of Energy Economics and Policy, 2023)
The objective of this study is to develop a model for forecasting energy consumption and to increase the effectiveness of Thailand’s sustainable development policy based on energy consumption by using the best model, the Path Analysis-Generalized Autoregressive Conditional Heteroscedasticity Model (Path-GARCH model). To improve the effectiveness of sustainability policies, the researcher has envisioned the final energy consumption over a 20-year period (AD 2023–2022) by defining a new scenario policy. Comparing the performance of the Path-GARCH model to other previous models, the Path-GARCH model was found to have the lowest mean absolute percentage error (MAPE) and root mean square error (RMSE) values. In addition, the study found that energy consumption continued to rise to 125,055 ktoe by 2042, with a growth rate of 115.05% between 2042 and 2023, which exceeded the carrying capacity limit of 90,000 ktoe. When a new scenario policy is implemented, however, the final energy consumption continues to rise to 74,091 ktoe (2042). Consequently, defining a new scenario policy is a crucial development guideline for enhancing the effectiveness of Thailand’s sustainable development policy.